Application of Multi-Criteria Decision Analysis in Determining Suitable Waste-To-Energy Technology for Awka, Anambra State (Journal of Geography, Meteorology and Environment, 2025)
This paper explored use of multi-criteria decision analysis (MCDA) to select waste-to-energy (WTE) technology for Awka, Nigeria necessary for addressing urgent urban solid waste issues. Urbanization has intensified waste generation, yet conventional waste management remains unsustainable despite government efforts. The study sought to identify suitable waste-to-energy (WtE) options through waste characterization, review of current practices, and identification of WtE choices. A survey design combining literature review data and primary data from questionnaires was used. Data was analysed through descriptive statistics and analytical hierarchy process (AHP) methodology. The AHP methodology was used to evaluate the WtE technologies and select the most appropriate technology for Awka. The WtE technologies were assessed through pairwise comparison of three main criteria and nine subcriteria assessed by 10 experts. Findings indicate that food waste is the most common waste type in Awka, followed by polyethylene/sachet water waste. The AHP-based pairwise comparison revealed that landfill gas is the most suitable WtE technology for Awka, followed by anaerobic digestion. The study portends the effectiveness of AHP for selecting sustainable waste management solutions and for resolving Awka’s waste challenges while promoting urban sustainability. The study recommends implementing WtE technology, adopting improved waste management methods, enhancing public engagement, and ensuring government support and policy enforcement towards circular economy in the State.
Keywords: waste-to-energy; multi-criteria decision analysis; analytical hierarchical process